PSURF-2, A Modified BAC Vector for Selective YAC Cloning and Functional Analysis. (July 1999) - Boyd, A.C.; Davidson, H.; Stevenson, B.; McLachlan, G.; Davidson-Smith, H.; Porteous, D.J.
A modified bacterial artificial chromosome (BAC) vector, pSURF-2, adapted for the selective subcloning of yeast artificial chromosome (YAC) sequences was constructed. DH10B-U, a pyrF derivative of the highly transformable E. coli strain DH10B was also constructed and used for the detection of Ura + recombinants carrying DNA linked to YAC right arms. The vector's properties were illustrated in two main ways. (i) An intact 25-kb YAC containing a mouse tyrosinase minigene was cloned into pSURF-2. Appropriately spliced tyrosinase RNA was detected by reverse transcription (RT)-PCR in extracts of cells transiently lipofected with the cloned YAC. (ii) Cells expressing human cystic fibrosis transmembrane conductance regulator ( CFTR ) from an integrated pSURF-2 recombinant containing a cDNA expression cassette were selected using the hygromycin-resistance (HyTK) marker of the vector and characterized by RT-PCR and immunoprecipitation. The unique I- Sce I site and HyTK marker of pSURF-2 are designed to facilitate subsequent functional studies of cloned DNA.